Moralitas Tindakan Ekonomi Pedagang Pasar Kamis Sungai Manau Kabupaten Merangin Provinsi Jambi - Inka Sri Yunara; Nazori Nazori; Nurfitri Martaliah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
An understanding of morality as distinguished through legality is found in Kant's moral philosophy. Based on his knowledge, morality is the similarity of nature or behavior to inner provisions or laws, namely what Kant sees as